Agro-ecological adaptation and participatory evaluation of multipurpose tree and shrub legumes in mid altitudes of Sud-Kivu, D.R. Congo - Katunga Musale, Dieudonné; Muhigwa, BJB; Kashala, KJC; Kambuyi, M; Nyongombe, N; Maass, Brigitte L.; Peters, Michael (Scientific Research Publishing, Inc., 2014)
Livestock is traditionally managed in mixed crop-livestock production systems in Sud-Kivu, D. R. Congo. Currently, livestock production is facing numerous constraints due to wars and insecurity in the country, with looting of animals, demographic pressure on natural resources, and lack of extension services. Multipurpose trees and shrubs with adequate forage quality could help overcome dry-season feed shortage. The objective of this research was to assess the agro-ecological adaptability of selected forage tree and shrub legumes combined with farmer participatory evaluation. The study was carried out at two distinct mid-altitude sites in Sud-Kivu. Trees and shrubs were planted randomly in eleven lines, with each species/accession consisting of nine plants split into three replications. Following a standardization cut after one year of growth, regular biomass harvests were performed every eight weeks during one year; Desmodium and Flemingia were cut at 0.5 m above soil surface, while Leucaena and Calliandra at 1 m. Before every harvest, plant height was measured and number of stems counted. Fresh leaf and stem biomass were weighted, sub samples dried and leaves analyzed for nutritive value. Results from agronomic evaluation show that Leucaena diversifolia ILRI 15551 and Leucaena leucocephala had the highest yield in the rainy season on fertile soil; during dry season, Leucaena diversifolia ILRI 15551 was superior. On poor soil, Flemingia macrophylla CIAT 17403 performed best in both seasons, however, its forage quality was relatively low. Forage tree and shrub legumes chosen by farmers were, in general, the same as those superior ones in agronomic evaluation.